Stable Casein‐Hydroxypropyl Cellulose Complexes at Low pH. Issue 4 (21st February 2016) - Ye, Ran; Cheng, Qunkang; Cai, Jianchao; Feng, Tao; Wang, Guanyu
Abstract: The effect of pH at acidic pH range on the stability of hydroxypropyl cellulose (HPC) and casein complexes was studied. Results suggested the occurrence of clear and transparent appearance of HPC‐casein complexes at pH 2.5 and 3. After storage for 3 weeks, the complexes maintained the excellent stability, as HPC molecules attached onto the surfaces of casein micelles through electrostatic interactions with strong positive charges resulted in an interparticle electrostatic repulsion, thereby preventing aggregation. The particle size, zeta potential analysis, turbidity, the protein concentration and viscosity confirmed the hypothesis. In addition, microscopic images revealed that the polysaccharide (HPC) particles adsorbed onto the surfaces of casein micelles, and casein‐HPC complexes were uniformly dispersed in the system. Moreover, the effects of the ionic strength on the stability of the complex were investigated. It was indicated that the particle size of casein‐HPC complexes at low concentration (2 mM) of NaCl remained the identical level ( P > 0.05), while the particle sizes significantly were increasing at the relatively higher concentrations (50 mM and 100 mM) of NaCl ( P < 0.05). Practical Applications: In this study, the casein‐HPC complexes at different pH values in aqueous systems were investigated. The results illustrate that the stable casein‐HPC complexes could be formed at low pH and the stability could be maintained over the duration of 3 weeks. The findings in this study would contribute to the production of acidified milk drinks in food industry.